Psychometric Properties and Criterion Validity of STEU-B and STEM-B in Chinese Context - Yan, Shuqun; Feng, Yuting; Xu, Yaoshan; Li, Yongjuan (Frontiers in Psychology, 2019)
Emotional intelligence (EI) has attracted increasing attention in organizational psychology. The aim of this study was to test the applicability of two performance-based emotional intelligence tests developed in western countries, namely, the brief versions of the Situational Test of Emotional Understanding (STEU-B) and the Situational Test of Emotional Management (STEM-B), in a sample of 904 Chinese employees. Specifically, item response theory (IRT) analyses were conducted. The item parameters along with the item and test information functions of the Chinese versions of the STEU-B and STEM-B were estimated. Moreover, the associations between the STEU-B and STEM-B scores and several work-related variables were examined. The results showed that the STEU-B and STEM-B had acceptable internal consistencies, and similar mean proportions of correct responses, item parameters, item information functions, and test information functions in China, as reported in previous studies. Furthermore, the scores were found to be related to the employees’ psychological strain, job-related affect, job satisfaction, and supervisor-rated job performance in a theoretically hypothesized manner. These findings suggested that the STEU-B and STEM-B might be useful measurements in future EI studies in the Chinese organizational context.